Versatile, high-power 460 nm laser system for Rydberg excitation of ultracold potassium - Arias Suárez, Alda Lisseth; Helmrich, Stephan; Lochead, Graham; Whitlock, Shannon (Optics express, 2017)
We present a versatile laser system which provides more than 1.5 W of narrowband light, tunable in the range from 455-463 nm. It consists of a commercial titanium-sapphire laser which is frequency doubled using resonant cavity second harmonic generation and stabilized to an external reference cavity. We demonstrate a wide wavelength tuning range combined with a narrow linewidth and low intensity noise. This laser system is ideally suited for atomic physics experiments such as two-photon excitation of Rydberg states of potassium atoms with principal quantum numbers n > 18. To demonstrate this we perform two-photon spectroscopy on ultracold potassium gases in which we observe an electromagnetically induced transparency resonance corresponding to the 35s1/2 state and verify the long-term stability of the laser system. Additionally, by performing spectroscopy in a magneto-optical trap we observe strong loss features corresponding to the excitation of s, p, d and higher-l states accessible due to a small electric field.